Faces in Context: Does Face Perception Depend on the Orientation of the Visual Scene?. (October 2016) - Taubert, Jessica; van Golde, Celine; Verstraten, Frans A. J.
The mechanisms held responsible for familiar face recognition are thought to be orientation dependent; inverted faces are more difficult to recognize than their upright counterparts. Although this effect of inversion has been investigated extensively, researchers have typically sliced faces from photographs and presented them in isolation. As such, it is not known whether the perceived orientation of a face is inherited from the visual scene in which it appears. Here, we address this question by measuring performance in a simultaneous same–different task while manipulating both the orientation of the faces and the scene. We found that the face inversion effect survived scene inversion. Nonetheless, an improvement in performance when the scene was upside down suggests that sensitivity to identity increased when the faces were more easily segmented from the scene. Thus, while these data identify congruency with the visual environment as a contributing factor in recognition performance, they imply different mechanisms operate on upright and inverted faces.